ANALISIS CURAH HUJAN RENCANA DENGAN MENGGUNAKAN DISTRIBUSI GUMBEL UNTUK WILAYAH KABUPATEN LAMPUNG SELATAN - Jarwinda Jarwinda (Journal of Science, Technology, and Visual Culture, 2021)
The research focuses on the rainfall analysis, which aims to obtain the maxima data of rainfall using annual and partial data series, and to calculate daily plan rainfall on various return periods using Gumbel Distribution. Daily rainfall data was obtained from the BMKG at the Raden Inten II meteorological station with a total of 10 years data (2010 - 2019). Data processing in this study was carried out using Microsoft Excel software. The results of the analysis show that the plan rainfall using annual series yields higher rainfall depth of 101.5 mm – 261.3 mm. Meanwhile, partial series data of 30 maxima results in lower rainfall depth of 85.1 mm - 199.2 mm.